STUDI KASUS PERILAKU SOCIAL WITHDRAWAL PADA ANAK USIA DINI - Pratiwi, Hanna Ririn (PG PAUD Universitas Negeri Surabaya, 2020)
This study focuses on children's problems in aspects of their social development. Children's social development is related to the child's ability to interact with friends, adults around them, or the wider environment. Social withdrawal or withdrawal is one of the behavioral disorders in children's social development. In this study, there is an overview, the causative factors, the obstacles that occur, the intervention, and the impact of the intervention on children who experience Social withdrawal. This research uses a qualitative case study method, which is a method of direct investigation and focuses on an event or activity intensively and in detail. This research is aimed at teachers and parents alike, in order to better understand every development that the child goes through, if there is a disturbance it should be resolved immediately